Healthy and Safe Food Education for Elementary School Students: A Program Implementation at SDN 104242 Lubuk Pakam - Hasni Yaturramadhan Harahap; Barita Aritonang; Shofian Syarifuddin; Chandra Pranata; Dicky Yuswardi Wiratma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Elementary school students' knowledge regarding the selection of healthy and safe food remains low, posing a risk to their nutritional status and health. Schools serve as effective settings for enhancing knowledge through nutrition and food safety education. Therefore, this community service activity aimed to increase the knowledge of students at SDN 104242 Lubuk Pakam regarding the importance of consuming healthy and safe food. Objective: This community service activity aimed to improve the knowledge and awareness of students at SDN 104242 Lubuk Pakam concerning the importance of consuming healthy and safe food. Methods: The program was implemented through a preliminary survey, educational sessions involving interactive lectures, discussions, meaning-making activities, and educational games, followed by an evaluation using pre-tests and post-tests administered to 55 students. Results: The community service activity, attended by 55 students from SDN 104242 Lubuk Pakam, demonstrated an increase in knowledge regarding healthy and safe food following the educational intervention. Pre-test results indicated that the majority of students fell into the